«Lina Morell, un cas apassionant» (1942-1965), de Jordi Valor. Una mostra de literatura de consolació durant la postguerra - Balaguer, Enric (Caplletra. Revista Internacional de Filologia, 2015)
This paper analyses Jordi Valor's novel within the post-war novel in the País Valencià and especially in relation to the rhetorical romance and the consolation literature which is produced during this period.